Comparison of Bio and Eco-technologies with Chemical Methods for Pre-treatment of Flax Fibers: Impact on Fiber Properties. Issue 4 (December 2014) - Camano, Sabela; Behary, Nemeshwaree; Vroman, Philippe; Campagne, Christine
Flax fibers, available as fiber bundles, are commonly used as fiber reinforcement in composite materials as a substitute for glass fibers. Pre-treatments are often necessary for improving fiber-resin adhesion, and also to facilitate fiber elementarization, and to improve fiber ability to be implemented in mechanical processes limiting fiber damages. This paper focuses on the impact of biotechnologies (effect of 2 different enzymes: a pectate lyase and a laccase) and of an ecotechnology (ultrasound with ethanol), compared to classical chemical pre-treatments (using aqueous NaOH and ammonia) on the final flax fiber bundle properties, before and after a carding process. Fiber surface properties (wettability and/or zeta potential values), fiber elementarization and mechanical properties vary with the type of treatment (chemical nature of product and conditions used). Fibers elementarised using pectate lyase and ultrasound/ethanol have a hydrophilic surface and a high water absorption capacity, and are also of highest quality in terms of increased fineness. Treatment with NaOH yields the poorest fiber bundle tenacity. Laccase enzyme yields long thick hydrophobic fibers having very low water absorption capacity, and the most neutral surface charge. Properties of flax fibers can be easily monitored using different pre-treatments resulting in fibers which would be suited for various final applications.